Hubungan Kapitalis di Tempat Produksi yang Tersembunyi: Studi Kasus Petani Kakao Sertifikasi di Desa Piriang Tapiko - Mappatunru, A; Fariaty, Citra N; Zainuddin, Sriwiyata Ismail (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Abstract: This paper aims to depict the formation of capitalist relations in the hidden abode of production within the cocoa sector in the Village of Piriang Tapiko. The research is based on data collected from field research using an explanatory qualitative method. Employing a Marxist political economy approach, this study reveals that: (1) The presence of cocoa plants has ensnared local farmers in the village of Piriang Tapiko in commodification of subsistence. However, this entanglement does not necessarily subject them to class differentiation, as believed by some Marxist scholars. (2) Despite undergoing commodification of subsistence and full integration into market relations, cocoa farmers in the village of Piriang Tapiko can still access the market freely and control their work processes and its outcomes independently. The fertile forest land shapes their self-reliance in confronting market forces. (3) The plummeting cocoa productivity due to plant diseases has separated them from control over the means of production and their output, ensnaring them in a concealed capitalist relation as unpaid labor through outsourcing mechanisms hierarchically controlled by Nestle in the certified cocoa commodity chain. Ultimately, the formation of capitalist relations in the village of Piriang Tapiko adds a unique dimension to the trajectory of capitalism's development in diverse contexts.